2006
DOI: 10.1097/01.aids.0000233572.59522.45
|View full text |Cite
|
Sign up to set email alerts
|

Virological response to a triple nucleoside/nucleotide analogue regimen over 48 weeks in HIV-1-infected adults in Africa

Abstract: Zidovudine/lamivudine/tenofovir has good virological efficacy in advanced HIV disease. In this population, who were infected with HIV-1 subtypes A, C or D, M184V with or without NAMs was the most common route to resistance, whereas K65R was identified less often.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(26 citation statements)
references
References 17 publications
5
21
0
Order By: Relevance
“…This prevalence is similar to some prior studies based in clinical cohorts from subtype C or mixed subtype infections, in which the K65R mutations ranged from 0 to 27% and duration on a TDF-containing regimen ranged from 324 to 1000 days (8;10;12;1821). Notably, our results are consistent with a modest increase in K65R associated with subtype C HIV, similar to the 16% prevalence reported in a multi-national analysis of subtype C HIV (10) and with overlapping confidence intervals with another study in Africa in which 27.7% of the 47 participants receiving TDF developed the K65R mutation (12).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This prevalence is similar to some prior studies based in clinical cohorts from subtype C or mixed subtype infections, in which the K65R mutations ranged from 0 to 27% and duration on a TDF-containing regimen ranged from 324 to 1000 days (8;10;12;1821). Notably, our results are consistent with a modest increase in K65R associated with subtype C HIV, similar to the 16% prevalence reported in a multi-national analysis of subtype C HIV (10) and with overlapping confidence intervals with another study in Africa in which 27.7% of the 47 participants receiving TDF developed the K65R mutation (12).…”
Section: Discussionsupporting
confidence: 88%
“…The 40 patients with amplified HIV RNA were all infected with subtype C HIV-1; 22 (55%) of whom had drug resistance mutations detected by population sequencing (Table 2). NNRTI mutations were the most common (21; 52%), followed by the M184V/I mutation (11, 28%; 10 with M184V and 1 with M184I). Five (12%; 95% confidence interval: 4.1–27%) patients had the K65R mutation, four of whom also had the M184V mutation.…”
Section: Resultsmentioning
confidence: 99%
“…In resource-limited settings male gender has been associated with later initiation of ART [60], defaulting [59], [61]-[62], non-adherence [63]-[64] and mortality [64]-[68]. The association between gender and viral suppression varies; some studies report an association between female gender and first-line viral suppression [69]-[70] others between male gender and second-line viral suppression [71], These studies are from different settings, from urban townships to rural programmes; while biological characteristics may contribute, the association with gender is likely to be influenced by societal determinants specific to each setting. Within the community programme we did not find any association between gender and second-line virological suppression, and we were unable to assess the role of gender within the workplace as the majority of patients were male.…”
Section: Discussionmentioning
confidence: 99%
“…Triple NRTI therapy has been shown to have inferior virological and immunological outcomes and a high risk of selection for resistance mutations in ART‐naïve adult patients 89. The ARROW study showed that children on a three‐NRTI maintenance regimen with 3TC, ABC and ZDV had inferior virological outcomes at week 144 and more ZDV‐related neutropenia, but no difference in disease progression or immunological outcomes when compared to NNRTI plus 3TC and ABC 71.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 99%